Osmotic Stress Uncovers Correlations and Dissociations Between Larval Zebrafish Anxiety Endophenotypes - Cheng, Ruey-Kuang; Tan, Jazlynn Xiu Min; Chua, Kai Xin; Tan, Cheryl Jia Xin; Wee, Caroline Lei (Frontiers in Molecular Neuroscience, 2022)
Larval zebrafish are often used to model anxiety disorders. However, since it is impossible to recapitulate the full complexity and heterogeneity of anxiety in this model, examining component endophenotypes is key to dissecting the mechanisms underlying anxiety. While individual anxiety endophenotypes have been examined in zebrafish, an understanding of the relationships between them is still lacking. Here, we examine the effects of osmotic stress on a range of anxiety endophenotypes such as thigmotaxis, dark avoidance, light-dark transitions, sleep, night startle and locomotion. We also report a novel assay for stress-induced anorexia that extends and improves on previously reported feeding assays. We show that acute (< 30 min) osmotic stress decreases feeding but has no effect on dark avoidance. Further, acute osmotic stress dose-dependently increases thigmotaxis and freezing in a light/dark choice condition, but not uniform light environmental context. Prolonged (> 2 hours) osmotic stress has similar suppressive effects on feeding while also significantly increases dark avoidance and sleep, with weaker effects on thigmotaxis and freezing. Notably, the correlations between anxiety endophenotypes were dependent on both salt and dark exposure, with increased dissociations at higher stressor intensities. Our results demonstrate context-dependent effects of osmotic stress on diverse anxiety endophenotypes, and highlight the importance of examining multiple endophenotypes in order to gain a more complete understanding of anxiety mechanisms.